Atypical lateralization of ERP response to native and non-native speech in infants at risk for autism spectrum disorder - Seery, Anne M. (Elsevier, 2012)
Language impairment is common in autism spectrum disorders (ASD) and is often accompanied by atypical neural lateralization. However, it is unclear when in development language impairment or atypical lateralization first emerges. To address these questions, we recorded event-related-potentials (ERPs) to native and non-native speech contrasts longitudinally in infants at risk for ASD (HRA) over the first year of life to determine whether atypical lateralization is present as an endophenotype early in development and whether these infants show delay in a very basic precursor of language acquisition: phonemic perceptual narrowing. ERP response for the HRA group to a non-native speech contrast revealed a trajectory of perceptual narrowing similar to a group of low-risk controls (LRC), suggesting that phonemic perceptual narrowing does not appear to be delayed in these high-risk infants. In contrast there were significant group differences in the development of lateralized ERP response to speech: between 6 and 12 months the LRC group displayed a lateralized response to the speech sounds, while the HRA group failed to display this pattern. We suggest the possibility that atypical lateralization to speech may be an ASD endophenotype over the first year of life.